The eloquence of responding to miracles on the breasts in the sermons of the Rightly Guided Caliphs (may God be pleased with them): "Study in Selected Models" - ismael, Muthanna; Younes, Ibaa (Humanities Journal of University of Zakho, 2021)
The religious public speaking is one of the oldest arts of literature, and one of the societies whose monument have been preserved until this day is not without its community. Because of its functional role and effective influence, a human relied on it to defend himself or his tribe with his tongue. He used to resort to it in many situations, such as exhortation to fight, calling for reconciliation, the judiciary, and other matters of social, political and economic life, so rhetoric was used in it as a tool to express what was wanted, and it had a great impact on the lives of individuals and societies, negatively or positively. The preacher's contact with the listener, which was adopted by the high-class nations and peoples as a way to persuade and provoke people; To adopt the goals and objectives of the preacher. As for the Arab nation before Islam, it was one of the finest things it reached at that time, but was the essence of their lives, until I shade it in a new era with the advent of Islam. In the speech of the Prophet’s era, its importance increased in the era of early Islam due to its strong connection with the divine messages as well as the preachers. Being their first tool in reporting. The Rightly Guided Caliphs (PBUTH) after the Prophet (PBUH) directed the members of the nation and spread the teachings of Islam through the art of public speaking. In addition, they had knights with their methods and phrases full of wonderful colors; Therefore, the aim of this research was to stand at one of the verbal enhancers, using (the response to First Hemistich and second Hemistich as a means to identify the secrets of the meanings that these sermons brought by studying and analyzing examples of them to find out how to employ this verbal enhancer in rhetoric.